The Relationship between Job Satisfaction and Work Performance of Personnel in Bangpoo Industrial Estate - สาพิมพ์, เกศกนก; โอภารอิทธิวงษ์, วิภารัศม์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to 1. Study the happiness of employees in the Bangpoo Industrial Estate 2. Study the efficiency of employees in the Bangpoo Industrial Estate 3. Compare the efficiency of employees in the Bangpoo Industrial Estate 4. Study the relationship between happiness of employees and the efficiency of employees in the Bangpoo Industrial Estate The sample group consisted of 400 employees in the Bangpoo Industrial Estate, Samut Prakan Province. Simple random sampling was used. The research instrument was a questionnaire. The statistics used for data analysis were frequency, percentage, mean, standard deviation, t-test, and F-test. The results of the research found that 1. Overall, the happiness of employees was at a high level. 2. Overall, the efficiency of employees was at a high level (4.32). 3. Employees with different genders, ages, and education levels had different efficiency. In terms of working age, average monthly income, and job positions, there was no difference in efficiency. 4. Happiness of employees had a moderate relationship with article code and personnel efficiency at a statistical level of 0.676**, with a statistical significance of 0.01.